Medical ozone therapy reduces oxidative stress and testicular damage in an experimental model of testicular torsion in rats - Mustafa Tusat; Ahmet Mentese; Selim Demir; Ahmet Alver; Mustafa Imamoglu (International Brazilian Journal of Urology)
ABSTRACT Objective: Testicular torsion (TT) refers to rotation of the testis and twisting of the spermatic cord. TT results in ischemia-reperfusion (I/R) injury involving increased oxidative stress, inflammation and apoptosis, and can even lead to infertility. The aim of this study was to investigate the effect of ozone therapy on testicular damage due to I/R injury in an experimental torsion model. Materials and Methods: 24 male Sprague-Dawley rats were divided into 3 groups; shamoperated, torsion/detorsion (T/D), and T/D+ozone. Ozone (1mg/kg) was injected intraperitoneally 120 minutes before detorsion and for the following 24h. Blood and tissue samples were collected at the end of 24h. Johnsen score, ischemia modified albumin (IMA), total antioxidant status (TAS), total oxidant status (TOS), and oxidative stress index (OSI) levels were determined. Results: Levels of IMA, TOS, OSI, and histopathological scores increased in the serum/tissue of the rats in the experimental T/D group. Serum IMA, TOS, and OSI levels and tissue histopathological scores were lower in the rats treated with ozone compared with the T/D group. Conclusion: Our study results suggest that ozone therapy may exhibit beneficial effects on both biochemical and histopathological findings. Clinical trials are now necessary to confirm this.